2011
DOI: 10.1093/rpd/ncq596
|View full text |Cite
|
Sign up to set email alerts
|

Dose evaluation of selective collimation effect in cephalography by measurement and Monte Carlo simulation

Abstract: Recently, simulations based on the Monte Carlo code have been increasingly applied for physics phenomena, patient dose and quality assurance of radiation systems. The objective of this study was to use Monte Carlo simulation and measurement to verify dose and dose reduction in cephalography. The collimator was constructed with 3-mm thick lead plate, and attached to the tube head to remove regions of disinterest in the radiation field. A digital phantom patient was constructed to evaluate patient dose. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…They reported ED reductions around 60%, which is comparable to our result. Lee et al, 26 using Monte Carlo simulation and dose measurements to evaluate a collimator similar to that of Gijbels et al, 24 also found around 60% ED reduction. From the literature, it can be concluded that only 40% of the ED of a non-collimated cephalogram contributes to its diagnostic value.…”
Section: Discussionmentioning
confidence: 88%
“…They reported ED reductions around 60%, which is comparable to our result. Lee et al, 26 using Monte Carlo simulation and dose measurements to evaluate a collimator similar to that of Gijbels et al, 24 also found around 60% ED reduction. From the literature, it can be concluded that only 40% of the ED of a non-collimated cephalogram contributes to its diagnostic value.…”
Section: Discussionmentioning
confidence: 88%
“…After each readout, the glass rod dosimeter was annealed at 400°C for 1 hr, followed by a gradual cooldown for the next measurement (22) . The glass rod dosimeter was inserted into a female anthropomorphic phantom (Radiology Support Devices, Long Beach, CA) (20,22‐24) . Four trials were performed with the phantom for each treatment modality.…”
Section: Methodsmentioning
confidence: 99%
“…The HDRK phantom was based on sectioned color photographs of an adult male cadaver that has high image resolution (Choi et al 2006, Kim et al 2008). The KTMAN-2 phantom has been used by Lee et al (2011) to measure the effects of selective collimation in cephalography. Kim et al (2010) from the Korea Atomic Energy Institute have developed a series of voxel phantoms of different body shapes in order to better calculate counting efficiencies for whole-body counters instead of using physical BOMAB phantom that has a fixed size.…”
Section: The Evolution Of Computational Phantomsmentioning
confidence: 99%